Prevalence of pulp gangrene cases in dental clinic of Kerambitan II, Tabanan Community Health Center period October 2024-March 2025: Prevalensi kasus gangren pulpa di poli gigi UPTD Puskesmas Kerambitan II, Tabanan periode Oktober 2024-Maret 2025 - Pramesti, Sang Ayu Putu Tata Aditya; Pratama, I Wayan Agus Wirya (Makassar Dental Journal PDGI Makassar, 2025)
The pulp tissue is highly susceptible to damage caused by microbial invasion, physical trauma, chemical agents, or thermal injury. This study explored the prevalence of pulp gangrene based on the time of visit, gender, and age of patients at the Dental Clinic of the Kerambitan II Community Health Centre, Tabanan, Bali, during the period October 2024 to March 2025, using observatio-nal methods and a cross-sectional approach. The total number of patient visits during this period was 892; 89 patients were diag-nosed with pulp gangrene (60.49%). The highest number of cases occurred in March 2025 (15.1%). More than 50% of patients were female and the 19-34 age group dominated (22.82%). It was concluded that there is a high prevalence of pulp gangrene in women and the productive age. Therefore, pulp capping and root canal treatment are required for patients with pulp gangrene.